Wood vinegar-loaded bio-based polyurethane foam with killing effect on blue-green algae
Through the bio-based polyurethane foam loaded with wood vinegar liquid, the coordinated effect of the pH-responsive sustained release of wood vinegar liquid and the quaternized chitosan is solved, and the existing algae removal methods are highly costly, time-consuming and labor-intensive or secondary pollution are achieved, achieving efficient, safe and environmentally friendly inhibitory effect on cyanobacteria.
Patent Information
- Application Number
- CN202510293419.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-13
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2045-03-13
AI Technical Summary
The existing algae removal methods have problems such as high cost, time-consuming, slow effect or serious secondary pollution, especially when the eutrophication of lake water bodies leads to the large reproduction of cyanobacteria, and lack of efficient and safe solutions.
The bio-based polyurethane foam loaded with wood vinegar liquid was used to prepare hydrophilic polyurethane foam by one-step foaming method, and the effective inhibition of cyanobacteria was achieved through the synergistic effect of the pH-responsive sustained release of wood vinegar liquid and the synergistic effect of quaternized chitosan.
It has achieved efficient killing of cyanobacteria, improved the utilization rate of wood vinegar liquid, reduced the risk of environmental pollution, and provided an environmentally friendly and economical algae removal method.
Smart Images

Figure CN119798606A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of blue algae treatment and organic waste utilization, and in particular to a bio-based polyurethane foam loaded with wood vinegar and having a killing effect on blue algae. Background Art
[0002] Eutrophication of lake waters causes cyanobacteria to multiply in large numbers from July to October each year, forming a tens-centimeter-thick covering layer on the surface of the water, causing algal blooms. Algal blooms can lead to deterioration of water quality, block filters, consume a large amount of dissolved oxygen in the water, and produce secondary metabolites, especially harmful metabolites such as microcystins, which not only have adverse effects on water bodies and aquatic organisms, but also restrict social and economic development.
[0003] At present, the common methods of removing blue algae are divided into physical method, chemical method and biological method. Physical method usually uses filtration, but it is often costly, time-consuming and labor-intensive; biological method has slow effect and is difficult to be universal for algae; chemical method such as coagulation based on iron salt or aluminum salt is simple and efficient, but secondary pollution is very serious. Therefore, efficient and safe algae removal methods are urgently needed to be developed. Summary of the invention
[0004] The purpose of the invention is to overcome the shortcomings of the existing algae removal method and effectively utilize the by-product of the carbon production process - wood vinegar to provide an environmentally friendly algae removal method.
[0005] The present invention solves the technical problem by adopting the following technical solution: The invention discloses a method for preparing a bio-based polyurethane foam loaded with wood vinegar and having a killing effect on blue algae, characterized in that the steps are as follows: (1) Add 1 part of chitosan, 5 parts of polyethylene glycol methyl ether and 25 parts of 1% acetic acid aqueous solution into a reactor, heat to 60-65°C, start stirring, react for 6-8 hours, and then dry at 110-130°C and -0.1MPa for 1-2 hours to obtain polyethylene glycol chitosan; (2) After mixing polyol, polyethylene glycol chitosan, quaternary ammonium salt chitosan, chemical foaming agent, foam stabilizer, amine catalyst, cell opener and chain extender, the mixture was stirred at 3000 r / min for 3-5 min, polyphenyl polymethylene polyisocyanate was added, the mixture was stirred at 3000 r / min for 10-15 s, poured into a mold for foaming, cured at 60°C for 2-4 h, and then placed at room temperature for 24 h to obtain a bio-based polyurethane foam material; (3) adding deionized water to dilute the wood vinegar to a concentration of 5%, and then soaking the bio-based polyurethane foam obtained above in 10 mL of 5% wood vinegar for 2-4 h to allow the polyurethane foam to absorb the wood vinegar, thereby obtaining a polyurethane foam loaded with wood vinegar.
[0006] Preferably, the polyurethane foam is prepared from the following main components, and the mass proportions of each component are: 48-50 parts of polyol, 30-35 parts of polyphenyl polymethylene polyisocyanate, 2-3 parts of polyethylene glycol chitosan, 1-2 parts of chain extender, 1-1.5 parts of quaternary ammonium salt chitosan, 1-2 parts of foam stabilizer, 0.3-0.5 parts of amine catalyst, 1-1.5 parts of chemical foaming agent, and 0.1-0.2 parts of cell opener.
[0007] Preferably, the polyol is any one of polylactic acid polyol with a number average molecular weight of 400-600 and polyethylene glycol with a number average molecular weight of 2000-3000, or a mixture of the two.
[0008] Preferably, the structural formula of the PEGylated chitosan is:
[0009] Where n1=10, n2=15.
[0010] Preferably, the isocyanate is polyphenylpolymethylene polyisocyanate (PAPI).
[0011] Preferably, the chain extender is any one of dimethylaminopropylamine diisopropyl alcohol (DPA) and N,N-dimethylethanolamine (DMEA) or a mixture of the two.
[0012] Preferably, the amine catalyst is N,N-dimethylcyclohexylamine or triethylenediamine.
[0013] Preferably, the polyurethane chemical foaming agent is deionized water.
[0014] Preferably, the foam stabilizer is AK8805.
[0015] Preferably, the polyurethane cell opener is ZLY-1900.
[0016] Preferably, the composition ratio of the wood vinegar has a certain range, and the wood vinegar contains about 80% to 9% water and about 10% to 20% organic components, wherein the organic components are composed of the following components by mass percentage: 30-50% acetic acid, 5-15% formic acid, 1-5% phenol, 5-15% 2-methoxyphenol, and 5-15% 2-methoxy-4-methylphenol.
[0017] Preferably, the test algae species is Microcystis aeruginosa (M. aeruginosa), purchased from the Institute of Hydrobiology, Chinese Academy of Sciences, with the number FACHB-1319.
[0018] Preferably, the cell density of Microcystis aeruginosa is 1.42×10 7 cells / L.
[0019] Preferably, a method for preparing a bio-based polyurethane foam loaded with wood vinegar and having a killing effect on cyanobacteria is used to prepare a bio-based polyurethane foam loaded with wood vinegar and having a killing effect on cyanobacteria.
[0020] The beneficial effects of the present invention are mainly reflected in the following aspects: Wood vinegar is a byproduct produced in the process of biomass carbon production. Organic acids and phenolic substances are the main organic substances in wood vinegar, and are also the main components that give wood vinegar sterilization, deodorization and antibacterial functions. However, directly adding wood vinegar is prone to cause excessive concentration in the local area, polluting the environment. At the same time, after adding wood vinegar, the self-oxidation or photodegradation of wood vinegar will be accelerated under natural conditions, making it unable to permanently inhibit algae growth. In order to overcome this problem, the present invention uses bio-based polylactic acid polyol and polyethylene glycol as soft segments, and prepares hydrophilic polyurethane foam with polyphenyl polymethylene polyisocyanate by a one-step foaming method. By regulating the mass ratio of polyethylene glycol to polylactic acid polyol, the foam has a high water absorption rate and can absorb a large amount of wood vinegar. At the same time, the tertiary amine group introduced in the foam is combined with acetic acid and phenolic substances in wood vinegar through dynamic covalent bonds to achieve pH responsiveness and slow release of wood vinegar, and the utilization rate of wood vinegar is greatly improved.
[0021] The surface of cyanobacteria cells carries a negative charge, which ensures their stable suspension and reproduction in water bodies due to electrostatic repulsion. Quaternary ammonium chitosan carries a positive charge that can eliminate the surface electrostatic effect of cyanobacteria cells, thereby causing flocculation of cyanobacteria. However, since quaternary ammonium chitosan cannot be recovered by directly adding chitosan into the water body, the algae removal efficiency is low. In order to overcome this problem, chitosan can be grafted onto polyols through chemical reactions. At the same time, quaternized chitosan can be added during the preparation of hydrophilic polyurethane foam by reacting chitosan polyols and polyisocyanates, which can increase the ability of polyurethane foam to kill cyanobacteria in a long-term manner. The synergistic killing of wood vinegar and quaternized chitosan in bio-based polyurethane foam can effectively curb the generation and proliferation of cyanobacteria in water bodies.
[0022] The process of the invention is simple and easy to implement. The wood vinegar used is obtained by condensing waste gas generated in the carbon production process, and the source is environmentally friendly, and an effective utilization method is provided for organic waste treatment. The present invention utilizes the water absorption of polyurethane foam to load wood vinegar in the polyurethane foam, which plays a role of slow release and greatly increases the contact time between wood vinegar and blue algae. The tertiary amine groups introduced into the foam utilized in the present invention are combined with acetic acid and phenolic substances in wood vinegar through dynamic covalent bonds, thereby achieving pH-responsive sustained release of wood vinegar, and greatly improving the utilization rate of wood vinegar; The invention provides the foam with a long-lasting antibacterial property through chitosan grafting modification and quaternization treatment, and finally realizes effective inhibition of blue algae in water bodies through the synergistic effect of the slow release of wood vinegar and the quaternized chitosan. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 : is a flow chart of the preparation method of the bio-based polyurethane foam of the present invention; Figure 2 : is the removal rate of Microcystis aeruginosa in each embodiment and comparative example; Figure 3 : Optical photographs of the Microcystis aeruginosa samples in various embodiments and comparative examples at different times; Figure 4 : It is a characterization diagram of the speed of releasing wood vinegar from polyurethane foam in each embodiment and comparative example. DETAILED DESCRIPTION
[0024] The following describes the embodiments of the present invention by specific examples, and those skilled in the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification. The present invention can also be implemented or applied by other different specific embodiments, and the details in this specification can also be modified or changed in various ways based on different viewpoints and applications without departing from the spirit of the present invention. It should be noted that the features in the following embodiments and embodiments can be combined with each other without conflict. It should also be understood that the terms used in the embodiments of the present invention are to describe specific specific embodiments, rather than to limit the scope of protection of the present invention.
[0025] In one embodiment of the present invention, the polyurethane foam is prepared from the following main components, and the mass proportions of each component are: 48-50 parts of polyol, 30-35 parts of polyphenyl polymethylene polyisocyanate, 2-3 parts of polyethylene glycol chitosan, 1-2 parts of chain extender, 1-1.5 parts of quaternary ammonium salt chitosan, 1-2 parts of foam stabilizer, 0.3-0.5 parts of amine catalyst, 1-1.5 parts of chemical foaming agent, and 0.1-0.2 parts of cell opener.
[0026] In one embodiment of the present invention, the polyol is any one or a combination of polylactic acid polyol with a number average molecular weight of 400-600 and polyethylene glycol with a number average molecular weight of 2000-3000. That is, the polyol can be selected from any one of the above-mentioned types, such as polylactic acid polyol and polyethylene glycol, and the polyol can also be the above-mentioned two compositions, wherein the mass ratio of polylactic acid polyol to polyethylene glycol is 1:3 or 1:2 or 1:1. Isocyanate is polyphenyl polymethylene polyisocyanate (PAPI). The chain extender is a mixture of one or two of dimethylaminopropylamine diisopropanol (DPA) and N,N-dimethylethanolamine (DMEA). That is, the chain extender can be selected from any one of the above-mentioned types, such as dimethylaminopropylamine diisopropanol and N,N-dimethylethanolamine, and the chain extender can also be the above-mentioned two compositions, wherein the mass ratio of the two is 1:1. The foam stabilizer is AK8805, and the amine catalyst is N,N-dimethylcyclohexylamine or triethylenediamine.
[0027] The algae species used in the experiment was Microcystis aeruginosa (M. aeruginosa), purchased from the Institute of Hydrobiology, Chinese Academy of Sciences, number FACHB-1319. After the algae species were purchased, they were cultured in BG-11 medium, and the expansion ratio was set to algae liquid: BG-11 medium = 1:3. The light intensity was controlled at 2000-2100lx using a photometer, the temperature was (25±0.5) ℃, and the light-dark ratio was 12 h:12 h. The cell density was observed using an optical microscope. The cell density of the cyanobacteria used in this experiment was 1.42×10 7 cells / L.
[0028] See also Figure 1 A method for preparing a bio-based polyurethane foam loaded with wood vinegar and having a killing effect on blue algae comprises the following steps: S1. By weight, 1 part of chitosan, 5 parts of polyethylene glycol methyl ether and 25 parts of 1% acetic acid aqueous solution were added to the reactor, the temperature was raised to 60-65 ° C, stirring was started, the reaction was continued for 6-8 hours, and then the reaction was continued at 110-130 ° C and -0.1 MPa for 1-2 hours to obtain polyethylene glycol chitosan; For example, the heating temperature can be any value within the above temperature range, such as 60°C, 63°C or 65°C, the stirring time can be any value within the above time range, such as 6 h, 7 h or 8 h, the dehydration temperature can be any value within the above temperature range, such as 110°C, 120°C or 130°C, and the drying time can be any value within the above time range, such as 1 h, 1.5 h or 2 h.
[0029] S2. After mixing polyol, polyethylene glycol chitosan, quaternary ammonium salt chitosan, chemical foaming agent, foam stabilizer, catalyst, cell opener and chain extender, stir at 3000 r / min for 3-5 min, add polyphenyl polymethylene polyisocyanate, stir at 3000 r / min for 10-15 s, pour into a mold for foaming, cure at 60 ° C for 2-4 h, and then place at room temperature for 24 h to obtain a bio-based polyurethane foam material; For example, the stirring time can be any value within the above time range, such as 3 min, 4 min or 5 min, and the curing time can be any value within the above time range, such as 2 h, 2.5 h or 4 h.
[0030] S3. Add deionized water to dilute the wood vinegar to a concentration of 5%, and then soak the bio-based polyurethane foam obtained above in 10 mL of 5% wood vinegar for 2-4 h to allow the polyurethane foam to absorb the wood vinegar to obtain a polyurethane foam loaded with wood vinegar; For example, the soaking time can be any value within the above time range, such as 2 h, 3 h or 4 h.
[0031] The wood vinegar is subjected to GC-MS detection, and the undiluted wood vinegar contains 80% to 90% water and 10% to 20% organic components, wherein the organic components are as follows by mass percentage: 30-50% acetic acid, 5-15% formic acid, 1-5% phenol, 5-15% 2-methoxyphenol, and 5-15% 2-methoxy-4-methylphenol.
[0032] The technical scheme of the present invention is described in detail below through several specific examples. Unless otherwise specified, the raw materials and reagents used in the following examples are all commercially available products, or can be prepared by conventional methods in the art, and the instruments used in the examples are all commercially available.
[0033] Example 1
[0034] By mass, 1 part of chitosan, 5 parts of polyethylene glycol methyl ether and 25 parts of 1% acetic acid aqueous solution were added to the reactor, the temperature was raised to 60-65 °C, stirring was started, the reaction was continued for 6-8 h, and then the reaction was continued at 110-130 °C and -0.1 MPa for 1-2 h to obtain PEGylated chitosan (PEG-g-CS).
[0035] The raw materials for preparing bio-based polyurethane foam include, by mass, 16 parts of polylactic acid polyol, 32 parts of polyethylene glycol, 35 parts of polyphenyl polymethylene polyisocyanate, 2 parts of polyethylene glycol chitosan, 1 part of quaternary ammonium salt chitosan, 1 part of foam stabilizer AK8805, 0.3 parts of amine catalyst triethylenediamine, 1 part of chemical foaming agent deionized water, 1 part of chain extender dimethylaminopropylamine diisopropanol, and 0.1 part of cell opener ZLY-1900.
[0036] Accurately weighed polyol, quaternary ammonium salt chitosan, polyethylene glycol chitosan, chemical foaming agent, foam stabilizer, amine catalyst, chain extender and pore opener are added to the paper cup in sequence, mixed evenly to obtain component A, put into the paper cup, and control the temperature at 37°C; weighed polyphenyl polymethylene polyisocyanate component B is added and stirred with a stirrer at a high speed of 3000 r / min. When the material turns white, pour the mixture of components A and B into a pre-prepared container, let it stand at room temperature for foaming, take out the obtained polyurethane foam, place it in a constant temperature blast drying oven at 60°C for curing for 2 h, and then leave it at room temperature for 24 h before cutting it into 3×3×1 cm squares.
[0037] Deionized water was added to dilute the wood vinegar to a concentration of 5%. The organic component of 5% wood vinegar was 1%, and the organic components by mass percentage were as follows: acetic acid 50%; formic acid 15%; phenol 5%; 2-methoxyphenol 15%; 2-methoxy-4-methylphenol 15%. The bio-based polyurethane foam obtained above was then immersed in 10 mL of 5% wood vinegar for 2 h to allow the polyurethane foam to absorb the wood vinegar, thereby obtaining a polyurethane foam loaded with wood vinegar.
[0038] Example 2
[0039] By weight, 1 part of chitosan, 5 parts of polyethylene glycol methyl ether and 25 parts of 1% acetic acid aqueous solution were added to the reactor, the temperature was raised to 60-65 ° C, stirring was started, and the reaction was carried out for 6-8 hours. Then, the reaction was dried at 110-130 ° C and -0.1 MPa for 1-2 hours to obtain polyethylene glycol chitosan (PEG-g-CS).
[0040] The raw materials for preparing bio-based polyurethane foam include, by mass, 12.5 parts of polylactic acid polyol, 37.5 parts of polyethylene glycol, 35 parts of polyphenyl polymethylene polyisocyanate, 2 parts of polyethylene glycol chitosan, 1 part of quaternary ammonium salt chitosan, 1 part of foam stabilizer AK8805, 0.3 parts of amine catalyst triethylenediamine, 1 part of chemical foaming agent deionized water, 1 part of chain extender dimethylaminopropylamine diisopropanol, and 0.1 part of cell opener ZLY-1900.
[0041] Accurately weighed polyol, quaternary ammonium salt chitosan, polyethylene glycol chitosan, chemical foaming agent, foam stabilizer, amine catalyst, chain extender and pore opener are added to the paper cup in sequence, mixed evenly to obtain component A, put into the paper cup, and control the temperature at 37°C; weighed polyphenyl polymethylene polyisocyanate component B is added and stirred with a stirrer at a high speed of 3000 r / min. When the material turns white, pour the mixture of components A and B into a pre-prepared container, let it stand at room temperature for foaming, take out the obtained polyurethane foam, place it in a constant temperature blast drying oven at 60°C for curing for 2 h, and then leave it at room temperature for 24 h before cutting it into 3×3×1 cm squares.
[0042] Deionized water was added to dilute the wood vinegar to a concentration of 5%. The organic component of 5% wood vinegar was 1%, and the organic components by mass percentage were as follows: acetic acid 50%; formic acid 15%; phenol 5%; 2-methoxyphenol 15%; 2-methoxy-4-methylphenol 15%. The bio-based polyurethane foam obtained above was then immersed in 10 mL of 5% wood vinegar for 2 h to allow the polyurethane foam to absorb the wood vinegar, thereby obtaining a polyurethane foam loaded with wood vinegar.
[0043] Comparative Example 1 Observe the cell density under an optical microscope. 7 The algae solution with cells / L was placed in a beaker and observed for 60 hours.
[0044] Comparative Example 2 Add deionized water to dilute the wood vinegar to a concentration of 5%. The organic components of 5% wood vinegar are 1%, and the organic components by mass percentage are as follows: acetic acid 15%; phenol 5%; formic acid 5%; 2-methoxyphenol 15%; 2-methoxy-4-methylphenol 15%. Observe the cell density under an optical microscope. 200 mL of cyanobacteria with a cell density of 1.42×10 7 cells / L of algae solution was placed in a beaker, and then 10 mL of 5% wood vinegar was added and finally observed for 60 h.
[0045] Comparative Example 3 The raw materials used in this example were dehydrated by first adding the polyol into a reactor equipped with a mechanical stirrer, placing it in an oil bath at 110°C, and stirring it for 2 hours in an environment with a vacuum degree of less than -0.1 MPa to remove water from the system.
[0046] The raw materials for preparing bio-based polyurethane foam include, by mass, 50 parts of polylactic acid polyol, 35 parts of polyphenyl polymethylene polyisocyanate, 1 part of foam stabilizer AK8805, 0.3 parts of amine catalyst triethylenediamine, 1 part of chemical foaming agent deionized water, 1 part of chain extender dimethylaminopropylamine diisopropanol, and 0.1 part of cell opener ZLY-1900.
[0047] Accurately weighed polyols, chemical foaming agents, foam stabilizers, catalysts, chain extenders and cell openers were added to the paper cups in sequence, mixed evenly to obtain component A, and placed in the paper cups, and the temperature was controlled at 37°C; weighed polyphenyl polymethylene polyisocyanate component B was added and stirred with a stirrer at a high speed of 3000 r / min. When the material turned white, the mixture of components A and B was poured into a pre-prepared container, and allowed to stand at room temperature for foaming. The obtained polyurethane foam was taken out and placed in a constant temperature blast drying oven for curing for 2 h, and then placed at room temperature for 24 h before being cut into 3×3×1 cm squares.
[0048] Deionized water was added to dilute the wood vinegar to a concentration of 5%. The organic component of 5% wood vinegar was 1%, and the organic components by mass percentage were as follows: acetic acid 50%; formic acid 15%; phenol 5%; 2-methoxyphenol 15%; 2-methoxy-4-methylphenol 15%. The bio-based polyurethane foam obtained above was then immersed in 10 mL of 5% wood vinegar for 2 h to allow the polyurethane foam to absorb the wood vinegar, thereby obtaining a polyurethane foam loaded with wood vinegar.
[0049] Comparative Example 4 The raw materials used in this example were dehydrated by first adding the polyol into a reactor equipped with a mechanical stirrer, placing it in an oil bath at 110°C, and stirring it for 2 hours in an environment with a vacuum degree of less than -0.1 MPa to remove water from the system.
[0050] The raw materials for preparing the bio-based polyurethane foam include, by weight: 50 parts of polyethylene glycol, 35 parts of polyphenyl polymethylene polyisocyanate, 1 part of foam stabilizer AK8805, 0.3 parts of amine catalyst triethylenediamine, 1 part of chemical foaming agent deionized water, and 0.1 part of cell opener ZLY-1900.
[0051] Add accurately weighed polyol, chemical foaming agent, foam stabilizer, catalyst and cell opener to the paper cup in turn, mix well to obtain component A, put it into the paper cup, and control the temperature at 37°C; add weighed polyphenyl polymethylene polyisocyanate component B and stir it with a stirrer at a high speed of 3000 r / min. When the material turns white, pour the mixture of components A and B into a pre-prepared container, let it stand at room temperature for foaming, take out the obtained polyurethane foam, put it in a constant temperature blast drying oven for curing for 2 hours, and then leave it at room temperature for 24 hours before cutting it into 3×3×1 cm squares.
[0052] Deionized water was added to dilute the wood vinegar to a concentration of 5%. The organic component of 5% wood vinegar was 1%, and the organic components by mass percentage were as follows: acetic acid 50%; formic acid 15%; phenol 5%; 2-methoxyphenol 15%; 2-methoxy-4-methylphenol 15%. The bio-based polyurethane foam obtained above was then immersed in 10 mL of 5% wood vinegar for 2 h to allow the polyurethane foam to absorb the wood vinegar, thereby obtaining a polyurethane foam loaded with wood vinegar.
[0053] Comparative Example 5 The raw materials used in this example were dehydrated by first adding the polyol into a reactor equipped with a mechanical stirrer, placing it in an oil bath at 110°C, and stirring it for 2 hours in an environment with a vacuum degree of less than -0.1 MPa to remove water from the system.
[0054] The raw materials for preparing bio-based polyurethane foam include, by mass, 25 parts of polylactic acid polyol, 25 parts of polyethylene glycol, 35 parts of polyphenyl polymethylene isocyanate, 1 part of foam stabilizer AK8805, 0.3 parts of amine catalyst triethylenediamine, 1 part of chemical foaming agent deionized water, 1 part of chain extender dimethylaminopropylamine diisopropanol, and 0.1 part of cell opener ZLY-19000.
[0055] Accurately weighed polyols, chemical foaming agents, foam stabilizers, amine catalysts, chain extenders and cell openers were added to the paper cups in sequence, mixed evenly to obtain component A, and placed in the paper cups, and the temperature was controlled at 37 °C; weighed polyphenyl polymethylene polyisocyanate component B was added and stirred with a stirrer at a high speed of 3000 r / min. When the material turned white, the mixture of components A and B was poured into a pre-prepared container, and allowed to stand at room temperature for foaming. The obtained polyurethane foam was taken out, placed in a constant temperature blast drying oven at 60 °C for curing for 2 h, and then placed at room temperature for 24 h before being cut into 3×3×1 cm squares.
[0056] Deionized water was added to dilute the wood vinegar to a concentration of 5%. The organic component of 5% wood vinegar was 1%, and the organic components by mass percentage were as follows: acetic acid 50%; formic acid 15%; phenol 5%; 2-methoxyphenol 15%; 2-methoxy-4-methylphenol 15%. The bio-based polyurethane foam obtained above was then immersed in 10 mL of 5% wood vinegar for 2 h to allow the polyurethane foam to absorb the wood vinegar, thereby obtaining a polyurethane foam loaded with wood vinegar.
[0057] Comparative Example 6 The raw materials for preparing the bio-based polyurethane foam include, by mass, 16 parts of polylactic acid polyol, 32 parts of polyethylene glycol, 35 parts of polyphenyl polymethylene polyisocyanate, 1 part of quaternary ammonium salt chitosan, 1 part of foam stabilizer AK8805, 0.3 parts of amine catalyst triethylenediamine, 1 part of chemical foaming agent deionized water, and 0.1 part of cell opener ZLY-1900.
[0058] Accurately weighed polyol, quaternary ammonium salt chitosan, chemical foaming agent, foam stabilizer, amine catalyst and pore opening agent were added to the paper cup in sequence, mixed evenly to obtain component A, and placed in the paper cup, and the temperature was controlled at 37°C; weighed polyphenyl polymethylene polyisocyanate component B was added and stirred with a stirrer at a high speed of 3000 r / min. When the material turned white, the mixture of components A and B was poured into a pre-prepared container, and allowed to stand at room temperature for foaming. The obtained polyurethane foam was taken out, placed in a constant temperature blast drying oven at 60°C for curing for 2 h, and then placed at room temperature for 24 h before being cut into 3×3×1 cm squares.
[0059] Deionized water was added to dilute the wood vinegar to a concentration of 5%. The organic component of 5% wood vinegar was 1%, and the organic components by mass percentage were as follows: acetic acid 50%; formic acid 15%; phenol 5%; 2-methoxyphenol 15%; 2-methoxy-4-methylphenol 15%. The bio-based polyurethane foam obtained above was then immersed in 10 mL of 5% wood vinegar for 2 h to allow the polyurethane foam to absorb the wood vinegar, thereby obtaining a polyurethane foam loaded with wood vinegar.
[0060] Comparative Example 7 The raw materials used in this example were dehydrated by first adding the polyol into a reactor equipped with a mechanical stirrer, placing it in an oil bath at 110°C, and stirring it for 2 hours in an environment with a vacuum degree of less than -0.1 MPa to remove water from the system.
[0061] The raw materials for preparing bio-based polyurethane foam include, by mass, 16 parts of polylactic acid polyol, 32 parts of polyethylene glycol, 35 parts of polyphenyl polymethylene polyisocyanate, 1 part of quaternary ammonium salt chitosan, 1 part of foam stabilizer AK8805, 0.3 parts of amine catalyst triethylenediamine, 1 part of chemical foaming agent deionized water, 1 part of chain extender dimethylaminopropylamine diisopropanol, and 0.1 part of cell opener ZLY-1900.
[0062] Accurately weighed polyol, quaternary ammonium salt chitosan, chemical foaming agent, foam stabilizer, amine catalyst, chain extender and cell opener are added to the paper cup in sequence, mixed evenly to obtain component A, put into the paper cup, and control the temperature at 37°C; weighed polyphenyl polymethylene polyisocyanate component B is added and stirred with a stirrer at a high speed of 3000 r / min. When the material turns white, pour the mixture of components A and B into a pre-prepared container, let it stand at room temperature for foaming, take out the obtained polyurethane foam, place it in a constant temperature blast drying oven at 60°C for curing for 2 h, and then leave it at room temperature for 24 h before cutting it into 3×3×1 cm squares.
[0063] Deionized water was added to dilute the wood vinegar to a concentration of 5%. The organic component of 5% wood vinegar was 1%, and the organic components by mass percentage were as follows: acetic acid 50%; formic acid 15%; phenol 5%; 2-methoxyphenol 15%; 2-methoxy-4-methylphenol 15%. The bio-based polyurethane foam obtained above was then immersed in 10 mL of 5% wood vinegar for 2 h to allow the polyurethane foam to absorb the wood vinegar, thereby obtaining a polyurethane foam loaded with wood vinegar.
[0064] Test Case Table 1 sample Water absorption Degradation rate Algae removal rate Example 1 510% 31% 84% Example 2 670% 40% 92% Comparative Example 1 / / 2% Comparative Example 2 / / 16% Comparative Example 3 80% 43% 3% Comparative Example 4 910% 7% 38% Comparative Example 5 340% 36% 63% Comparative Example 6 470% 30% 70% Comparative Example 7 480% 21% 74% Water absorption test: The water absorption performance of the polyurethane foams of Examples 1-2 and Comparative Examples 1-7 was tested. The foam sheets were cut into 3×3×1 cm squares, dried in an oven for 24 h, and initially weighed Y I Then, it was immersed in 120 ml of distilled water. After equilibration at 37 °C for 48 h, the sample was removed from the water, suspended for 10 s to allow free drainage, excess water was absorbed with paper, and then weighed again to obtain Y W The water absorption rate Y is shown in formula (1): Y=(Y W -Y I ) / Y I ×100% (1); In formula (1): Y = water absorption; Y I = initial mass of foam; Y W = mass after water absorption. The results are shown in Table 1. The test results show that the water absorption performance of the bio-based polyurethane foam prepared in Examples 1-2 improves with the increase of the content of polyethylene glycol. Comparative Example 3 has poor hydrophilicity due to the presence of only polylactic acid polyol, while Comparative Example 4 has good hydrophilicity and the highest water absorption rate due to the presence of only polyethylene glycol. The water absorption performance of the bio-based polyurethane foam prepared in Comparative Examples 5-7 improves with the increase of the content of polyethylene glycol.
[0065] Algae removal rate test: The algae removal performance of Examples 1-2 and Comparative Examples 1-7 was tested. The polyurethane foam loaded with wood vinegar was placed in 200 mL of a cyanobacteria cell density of 1.42×10 7 cells / L beaker for 60 h. First, take 5 mL of the treated algae solution from the beaker and centrifuge it at 4000 r / min for 10 min, and remove the supernatant. Secondly, resuspend the microalgae in 90% acetone (5 mL) and then store it in the dark at 4 ℃ for 24 h. Finally, centrifuge the suspension at 4000 r / min for 15 min. Collect the supernatant for the determination of chlorophyll a concentration. Use a UV-visible spectrophotometer to record the absorbance of the acetone solution at 630, 645, 663 and 750 nm. The chlorophyll a concentration (mg / L) is calculated by the following equation: C = [11.64 × (OD 663 -OD 750 )-2.16×(OD 645 -OD 750 )+0.10×(OD 630 -OD 750 )]×V1 / V (2); In formula (2): C: chlorophyll a concentration, mg / L; OD: absorbance at each wavelength; V1: volume of acetone-based extract, mL; V: sample volume, mL.
[0066] The algae removal efficiency W is shown in formula (3): W=(1-C t / C0)×100% (3); In formula (3): W = algae removal rate; C t = Chlorophyll a concentration of the algae solution after treatment; C0 = initial chlorophyll a concentration of the algae solution.
[0067] The algae removal results are shown in Table 1 and Figure 2 , the test results show that the algae removal rate of the bio-based polyurethane foam slow-release wood vinegar prepared in Examples 1 and 2 is significantly higher than that of Comparative Examples 1-4. Examples 1 and 2 contain quaternary ammonium chitosan and polyethylene glycol chitosan, and the foam slow-release wood vinegar is slow, so the algae removal efficiency is high. Comparative Example 2 is to directly put wood vinegar, and the algae removal efficiency is low; Comparative Example 3 only contains polylactic acid polyol, which has poor hydrophilicity, low wood vinegar release efficiency, and no polyethylene glycol chitosan and quaternary ammonium chitosan; Comparative Example 4 contains polyethylene glycol but no dimethylaminopropylamine diisopropanol chain extender, wood vinegar release is fast, and there is no polyethylene glycol chitosan and quaternary ammonium chitosan; Comparative Example 5 does not contain polyethylene glycol chitosan and quaternary ammonium chitosan, all resulting in low algae removal efficiency. Comparative Example 6 does not contain polyethylene glycol chitosan, so the algae removal efficiency is lower than that of Example 1.
[0068] Degradation rate test: The degradation performance of the polyurethanes of Examples 1-2 and Comparative Examples 1-7 was tested. The dried polyurethane foams were cut into a shape of 1 cm×1 cm×0.5 cm and weighed (W0). Then, they were immersed in SBF (15 ml) and placed in a shaking culture at 37°C (120 r / min) for one week. Then, the foams were transferred to a vacuum drying oven at 37°C and dried for 72 hours. The weight (W0) was 0.1447 W. T The test lasted for five cycles. The degradation rate (W%) is shown in formula (4): W%=(W0-W T ) / W0×100% (4); In formula (4): W% = degradation rate; W0 = initial mass; W T =Mass of foam after degradation.
[0069] The results are shown in Table 1. The test results show that the algae removal rate of the bio-based polyurethane foam slow-release wood vinegar prepared in Examples 1-2 is significantly higher than that of Comparative Example 4. Because Comparative Example 4 only contains polyethylene glycol and no bio-based polyol, the degradation rates of Examples 1 and 2 are higher than those of Comparative Examples 6 and 7 because they contain polyethylene glycol chitosan, which promotes its degradation. The reason why the degradation rate of Comparative Example 3 is higher is that it only contains polylactic acid polyol, so the degradation rate is higher.
[0070] Sustained release rate test: Add deionized water diluted to 0.1% of wood vinegar into a beaker. Then place the polyurethane foam adsorbed with wood vinegar in the beaker and use a UV-visible spectrophotometer to test the change in absorbance of phenolic substances in the water at 275 nm every 6 hours to characterize the speed at which the foam releases wood vinegar. The results are as follows: Figure 4 As shown. It can be seen from the figure that the speed at which the foams of Examples 1 to 2 release wood vinegar is slower than that of Comparative Example 4, because Comparative Example 4 only uses polyethylene glycol as a polyol, and its excellent hydrophilicity can quickly exchange with external water bodies. At the same time, it does not contain dimethylaminopropylamine diisopropanol, and the acids and phenols in the wood vinegar cannot achieve the pH-responsive sustained release of the wood vinegar. The release speed of Example 2 is faster than that of Comparative Examples 5 and 7 because it has a high polyethylene glycol content and good hydrophilicity. The fast release speed of Comparative Example 6 is because it does not contain dimethylaminopropylamine diisopropanol, and the acids and phenols in the wood vinegar cannot achieve the pH-responsive sustained release of the wood vinegar.
[0071] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A bio-based polyurethane foam loaded with wood vinegar having a killing effect on blue algae, characterized in that: Bio-based polyurethane foam includes the following components, and the mass fraction of each component is: 48-50 parts of polyol; 30-35 parts of polyphenyl polymethylene polyisocyanate; 2-3 parts of PEGylated chitosan; 1-2 parts of chain extender; 1-1.5 parts of quaternary ammonium salt chitosan; 1-2 parts of foam stabilizer; 0.3-0.5 parts of amine catalyst; 1-1.5 parts of chemical foaming agent; 0.1-0.2 parts of cell opening agent; The bio-based polyurethane foam is soaked in wood vinegar to obtain the wood vinegar-loaded bio-based polyurethane foam which has a killing effect on blue algae.
2. The bio-based polyurethane foam loaded with wood vinegar having a killing effect on blue algae according to claim 1, characterized in that: The polyol is any one of polylactic acid polyol with a number average molecular weight of 400-600 and polyethylene glycol with a number average molecular weight of 2000-3000 or a mixture of the two.
3. The bio-based polyurethane foam loaded with wood vinegar having a killing effect on blue algae according to claim 1, characterized in that: The structural formula of the PEGylated chitosan is: ; Where n1=10, n2=15.
4. The bio-based polyurethane foam loaded with wood vinegar having a killing effect on blue algae according to claim 1, characterized in that: The chain extender is any one of dimethylaminopropylamine, diisopropyl alcohol and N,N-dimethylethanolamine or a mixture of the two.
5. The bio-based polyurethane foam loaded with wood vinegar having a killing effect on blue algae according to claim 1, characterized in that: The amine catalyst is N,N-dimethylcyclohexylamine or triethylenediamine.
6. The bio-based polyurethane foam loaded with wood vinegar having a killing effect on blue algae according to claim 1, characterized in that: The wood vinegar contains 80% to 90% of water and 10% to 20% of organic components; the organic components are composed of the following by mass percentage: 30-50% of acetic acid, 5-15% of formic acid, 1-5% of phenol, 5-15% of 2-methoxyphenol, and 5-15% of 2-methoxy-4-methylphenol.
7. A method for preparing a bio-based polyurethane foam loaded with wood vinegar and having a killing effect on blue algae, characterized in that: The method is applied to prepare a bio-based polyurethane foam loaded with wood vinegar and having a killing effect on blue algae as described in any one of claims 1 to 6, comprising the following steps: Step (1), by weight, adding 1 part of chitosan, 5 parts of polyethylene glycol methyl ether and 25 parts of 1% acetic acid aqueous solution into a reactor, heating to 60-65°C, stirring, reacting for 6-8 hours, and drying at 110-130°C and -0.1MPa for 1-2 hours to obtain polyethylene glycol chitosan; Step (2), after mixing polyethylene glycol, polylactic acid polyol, polyethylene glycol chitosan, quaternary ammonium salt chitosan, chemical foaming agent, foam stabilizer, amine catalyst, cell opener and chain extender, stirring at 3000 r / min for 3-5 min, adding polyphenyl polymethylene polyisocyanate, stirring at 3000 r / min for 10-15 s, pouring into a mold for foaming, curing at 60°C for 2-4 h, and then leaving at room temperature for 24 h to obtain a bio-based polyurethane foam material; Step (3), adding deionized water to dilute the wood vinegar to a concentration of 5%, and soaking the bio-based polyurethane foam obtained in step (2) in 10 mL of 5% wood vinegar for 2-4 h to allow the polyurethane foam to absorb the wood vinegar, thereby obtaining a polyurethane foam loaded with wood vinegar.
Citation Information
Patent Citations
Method for controlling cyanobacteria bloom
CN102134126A
Amphipathy polyethylene glycol stem grafting chitosan copolymer and preparation method and application thereof
CN102504046A
Preparation method of quaternary ammonium salt chitosan and organic silicon composite modified cationic water-based polyurethane fixing agent
CN103709364A
Application of pegylation chitosan serving as nucleic acid vector
CN103725713A
High-aperture-ratio biomass-based rigid polyurethane foam and preparation method thereof
CN107353389A